Potential And Challenges Of Organic Agrotourism In Sambangan Tourism Village - Firman Sinaga; Komang Shanty Muni Parwati; Komang Trigita Juliastari (Jurnal Ilmiah Hospitality Management, 2026)
This study aims to identify the potential and challenges of developing organic farming-based agrotourism in Sambangan Tourism Village, Buleleng, Bali. This village has abundant natural resources, fertile agricultural land, and high local community support for sustainable agricultural practices. The main potential includes the existence of organic commodities such as rice, vegetables, and tropical fruits which can become educational tourist attractions while also supporting the local economy. However, this study also identified a number of challenges, including limited infrastructure, farmers' low knowledge of digital marketing, and the need for synergy between the government, communities, and the private sector. Through SWOT analysis, this study confirms that Sambangan Village is in a strategic position to develop organic agrotourism with a stable growth strategy. The results of this research are expected to be the basis for planning policies and programs for developing sustainable tourism villages.